Enforceability of the sanction of dismissal of dignitaries for faulty administrative responsibility - Reyna Zambrano, María Yokir; Pazmiño Castro, Frank Alexander; Santana Mendoza, Faber Alexito (Frónesis, 2022)
Analyzing the enforceability of the resolutions of the Comptroller General of the State that imposes the sanction of dismissal of dignitaries is the objective of the study. The qualitative research contains the review of the specialized doctrine, for which Administrative Law was related to core aspects of the exercise of political rights, estimating the complex faculty of the Comptroller General of the State in determining the sanction of removal of popularly elected public servants. The importance of the bibliographic review is the scarce scientific production in the Ecuadorian legal field that accounts for the correspondence between these study categories. The analysis and discussion of the information warns of the need to harmonize the norms that regulate the organization, operation and powers of the State and the responsibility of all public servants in the exercise of their functions. In conclusion, the mission of the Comptroller General of the State to ensure the proper use of public resources is positively valued, however, it is impossible to execute the sanction of dismissal of dignitaries of popular election if there is not a legal adaptation that does not violate the enjoyment of the participation rights of dignitaries and voters.